Hydraulic conductivity of a Red Latosol under fallow and intensive cultivation - Angelotti Netto, Antonio; Fernandes, Edemo João (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The understanding and the prediction of the water flow in the soil are essential for its agricultural and environmental management. This work aimed to determine and to compare the hydraulic conductivity obtained by the instantaneous profile method in the field in a soil kept in fallow for six years and other one with intensive cultivation for the same period. The technique of Hillel was used to obtain the hydraulic conductivity. The water content in Red Latosol (Rhodic Eutrudox) was determined by the conversion of the values of matric potential in water content according to the van Genuchten equation. The matric potential determination was accomplished in the depths of 0.2, 0.4, 0.6, 0.8 and 1.0 m, during 24 days. The greatest values of hydraulic conductivity to the depth of 1.0 m were achieved under fallow conditions. The parameter saturated hydraulic conductivity was responsible for the greatest values of the function K(q) determined in all depths, independently of the water content of the soil used as reference.